1979
DOI: 10.1677/joe.0.0810061
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Ovarian Hormones During the Oestrous Cycle of the Sheep and Cow

Abstract: Measurements were made of the plasma concentrations of testosterone, progesterone and oestradiol-17 beta during the oestrous cycle of the ewe, and of the plasma concentrations of testosterone and progesterone during the oestrous cycle of the heifer. The maximum concentration of progesterone in the heifer was nearly twice that in the ewe. The maximum concentration of testosterone was similar in both species and occurred at the onset of luteolysis; in the ewe the peak concentration of 19.5 ng/ml plasma was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…In agreement with previous studies, concentrations of estradiol-17p in two Asian elephants in the present study are less than 20 pgiml except a value in one animal (Daya). The levels of circulating estradiol-17P in Asian elephants in the present study falls within the range reported in cyclic cows [Chenault et al, 1975;Herriman et al, 1979;Schallenberger et al, 1985;Quirk and Fortune, 1986;Kaneko et al, 19901. The difference in estradiol-17p results between this and earlier reports probably stems from the RIA method [Taya et al, 19851 with greater sensitivity used in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with previous studies, concentrations of estradiol-17p in two Asian elephants in the present study are less than 20 pgiml except a value in one animal (Daya). The levels of circulating estradiol-17P in Asian elephants in the present study falls within the range reported in cyclic cows [Chenault et al, 1975;Herriman et al, 1979;Schallenberger et al, 1985;Quirk and Fortune, 1986;Kaneko et al, 19901. The difference in estradiol-17p results between this and earlier reports probably stems from the RIA method [Taya et al, 19851 with greater sensitivity used in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Similar differences in progesterone levels were reported by Bauernfeind & Holtz (1991) in Dairy x Boer in Germany. In the ewe, similar differences in progesterone levels were reported by Herriman et al (1979) in Dorset Horn x Finnish Landrace in the UK, and in some prolific sheep breeds in Poland (Reklewska et al 1988). Using radioimmunoassay, Zarkawi (1997) also found differences in the maximum progesterone level in the Syrian Awassi ewes during the luteal phase of the oestrous cycle, with a range of 5.8-18.00 nmol I" 1 .…”
Section: Discussionsupporting
confidence: 52%
“…The highest levels of testosterone in the cyclic cow and ewe are during the luteal phase and just before CL regression Hoffman & Rattenberger, 1977;Herriman, Harwood, Mallinson & Heitzman, 1979). We found differences for the release of testosterone on Days -8 to -4 and Days -13 to -9: the significant increases in spikes of testosterone release before CL regression concur with the increases noted by in peripheral testosterone levels during the oestrous cycle.…”
Section: Discussionsupporting
confidence: 53%